Electro-optic, dielectric and optical studies of NiFe2O4-ferroelectric liquid crystal: a soft magnetoelectric material. Issue 11 (1st September 2016) - Khushboo,; Sharma, Puneet; Malik, Praveen; Raina, K. K.
ABSTRACT: In the present study, magnetic nanoparticles (NP, nickel ferrite) in different concentrations into ferroelectric liquid crystal (FLC) mixture have been prepared and studied. The effect of nickel ferrite concentration on the electro-optic, dielectric and optical properties of FLC mixture has been studied and discussed. An improvement in spontaneous polarization, response time in nickel ferrite-FLC-doped samples compared to FLC is observed and explained on the basis of dipole moment and anchoring phenomena. The Goldstone mode (GM) is detected in all samples and follows a Debye-type relaxation behaviour. A twofold increase in relaxation frequency for the doped sample rather than the pure sample has been observed. The band gap was found more or less independent of doping concentration. The activation energy (Ea ) also decreases on increasing the doping amount. GRAPHICAL ABSTRACT: